Thermoluminescence Dosimetric Properties of Ge- and Er-Doped Optical Fibres and Their Application in The Measurement of Depth -Dose in Solid Water Phanthom - Amin, Y.M.; Abdulla, Y.A.; Khoo, B.H. (Korean Association for Radiation Protection, 2001)
The dosimetric properties of Ge- and Er-doped optical fibres are studied. The Ge-doped fibre is found to be more sensitive to radiation and there is little fading of TL signal compared with Er-doped fibre. The Ge- and Er-doped fibres showed a linear response over a range of to about 120 Gy and to about 250Gy respectively. The Ge-doped fibre is found to be dose-rate independent both for photons and electron beams of energy ranging from 6 to 10 MeV and 6 to 12 MeV respectively. The fibre is energy independent for energy greater than for photon or 0.1 MeV for electron beam. From the depth-dose measurement, it was found that the position of maximum dose, dmax, increased with increasing energy ranging from and for 6 MeV and 10 MeV photons respectively. The central axis percentage depth dose at 10 cm depth was found to be in good agreement with the value obtained using ionization chamber.